(untitled) (Journal of Economic Research & Business Administration, 2020)
Excessive differentiation at the level of socio-economic development of the regions leads to the disintegration of a single socio-economic space and the emergence of territorial imbalances in economic and social structures, which entails a decrease in the functioning efficiency of not only regional, but also the national economy as a whole. Since territorial socio-economic imbalance is accompanied by a number of negative consequences, their overcoming is defined as an important direction of state policy in most countries and regions of the world. Therefore, the aim of the article is to study different ways to minimize the negative effects of interregional differentiation, which exacerbates social tension and impedes balanced economic development, by identifying factors affecting the occurrence of socio-economic imbalances. Based on the results of the study, specific recommendations were formulated to eliminate the identified negative consequences of interregional differentiation in terms of GRP per capita on the development of regions, the influence of investment activity on distinction in their development is investigated, and the role of financial resources in smoothing interregional differentiation is justified. The theoretical and methodological basis of this study is the work of domestic and foreign scientists on the theory and practice of inequality in the socio-economic development of regions. The study used methods of comparative economic analysis, expert assessment methodology and a systematic approach. The article substantiates the thesis that the reduction of differentiation between the regions of Kazakhstan will allow the socio-economic system of the regions to function efficiently, improve the quality of life of the population, and reduce social tension.